Komisi konstitusi merupakan suatu kebohongan publik : pidato Dr. A.S.S. Tambunan, S.H. di Gedung MPR/DPR-RI. - Tambunan, A. S. S. (Arifin Sari Sarunganlan), 1924-; Indonesia ([Jakarta] : Forum Kajian Ilmiah Konstitusi, 2003)
On the need for amendment to the Indonesian 1945 Constitution and critics on proposed contitution commission in Indonesia; speech of A.S.S. Tambunan, a politician.
Mode of access: Internet.
Keywords: Constitutional law -- Indonesia; Constitutional amendments -- Indonesia; Constitutions -- Indonesia